SPK Pemilihan Calon Mekanik pada Perusahaan Transportasi Antar Kota Menggunakan Metode Analytic Hierarki Process (AHP) - Sanriomi Sintaro; Tien Yulianti (Jurnal Media Celebes, 2024)
Perusahaan XYZ operates as a transportation company that serves inter-city and provincial routes across Sumatra, Java and Bali. Prioritizing service quality and passenger comfort, the company relies on safe and comfortable transportation facilities. To ensure the reliability of their fleet, regular maintenance is essential. However, the large number of vehicles and technicians requires an effective recruiting system to identify skilled and reliable personnel. Historically, mechanical selection at Perusahaan XYZ mainly relied on reviewing application files submitted by prospective mechanics. Many technicians are hired because of family ties, resulting in a lack of understanding of the maintenance details outlined in standard operating procedures (SOP). As a result, travel inconveniences often arise due to a lack of professionally trained technical personnel during maintenance procedures. To answer this challenge, a decision support system is needed that will be used to select mechanics. The system design was implemented using Java with MySQL as the database. The aim of this research is to develop an application that is able to solve existing problems, especially in the decision-making process for recruiting mechanical staff, ensuring the acceptance of qualified candidates. The proposed solution involves the creation of a computerized decision support system using the analytical hierarchy process (AHP) method. Through this, it is hoped that the mechanical acceptance process will experience improved decision making, resulting in higher quality selection based on research conducted at Perusahaan XYZ.